The Influence of Return on Equity, Debt to Assets Ratio, Current Ratio, and Cash Position on Dividend Payout Ratio - Aqmalia, Anggun Nur Hanna; Anita, Widya Febryari (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
This study aims to determine the influence of Return on Equity (ROE), Debt to Assets Ratio (DAR), Current Ratio (CR), and Cash Position (CP) on the Dividend Payout Ratio (DPR). The sample used in this research consists of Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. A total of 10 companies were sampled, resulting in 40 observational data points. The research method employed includes classical assumption tests, multiple linear regression analysis, and hypothesis testing, processed using IBM SPSS Statistics 26. The results of this study indicate that ROE, DAR, and CR do not have a significant influence on DPR. However, CP has a significant effect on DPR. Simultaneously, ROE, DAR, CR, and CP collectively have a significant impact on DPR.